2019
DOI: 10.1016/s2542-5196(19)30090-7
|View full text |Cite
|
Sign up to set email alerts
|

Trends in temperature-related age-specific and sex-specific mortality from cardiovascular diseases in Spain: a national time-series analysis

Abstract: Background Climate change driven by human activities has increased annual temperatures in Spain by around 1°C since 1980. However, little is known regarding the extent to which the association between temperature and mortality has changed among the most susceptible population groups as a result of the rapidly warming climate. We aimed to assess trends in temperature-related cardiovascular disease mortality in Spain by sex and age, and we investigated the association between climate warming and changes in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
141
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(165 citation statements)
references
References 41 publications
(56 reference statements)
19
141
1
4
Order By: Relevance
“…3). Similar results have also been reported in other countries such as Japan 34 and Spain 32 . Chung found that from 1972 to 2012, MMT rose about 4.8°C in Japan, and the MFT in the same period has increased 5°C.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…3). Similar results have also been reported in other countries such as Japan 34 and Spain 32 . Chung found that from 1972 to 2012, MMT rose about 4.8°C in Japan, and the MFT in the same period has increased 5°C.…”
Section: Discussionsupporting
confidence: 91%
“…We calculated the MFTs of these locations during the same period. We found that: (1) In most locations, the temporal trends of MMT and MFT are consistent 9,31-35 ; (2) The MMT and MFT have increased in most locations of the studied countries 9,31-35 ; (3) Although in some locations MMT did not change or reduced, MFT had the similar trend in most of these locations 32,35 . For example, Donaldson found that from 1972 to 1997, MMTs rose 3.6°C in North Carolina, 2.7°C in Southeast…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Both cold temperatures [1,2] and hot temperature extremes [3] are associated with higher mortality rates. Therefore, a kind of U-shaped association between daily temperature and daily number of deaths is expected [4,5]. Previous evidence suggests that the optimal temperature, that is the temperature with the lowest number of deaths, is higher in areas with warmer climate and lower in areas with colder climate [6,7].…”
Section: Introductionmentioning
confidence: 97%
“…Though several studies predict that global warming will lead to an increase in heat-related mortality and a decrease in cold-related mortality in the future, only a few consider minimum mortality temperature (MMT) as a reference value to estimate future relative risks or attributable mortality [1,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%